“The folklore treasure there is astounding”: Reappraising Margaret Sargent McTaggart’s Contribution to the Documentation of Newfoundland Folksong at Mid-Century - Guigné, Anna (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2007)
AbstractIn 1949, anthropologist Marius Barbeau recruited Margaret Sargent, a young classically trained musician from Ontario to work for him at the National Museum of Canada. As the first ever musicologist to be employed by this institution, Sargent’s first task was to transfer Barbeau’s wax cylinder sound recordings to magnetic tape. While working on Barbeau’s massive collection, Sargent became interested in collecting folksongs and proposed to him the idea of going to Newfoundland to do research. With Barbeau’s support, in 1950 she spent eight weeks in the province, collecting folksongs, fiddle tunes, and other folklore materials mainly in St. John’s and Branch. Despite launching the first Canadian funded research into Newfoundland’s folksong traditions, little is known about Sargent’s activities for the National Museum mainly because she published nothing of her Newfoundland work. Instead, her successor Kenneth Peacock is often viewed as launching this research. Although Peacock later visited the province six times, eventually publishing a three-volume collection Songs of the Newfoundland Outports (1965), it was Sargent who initiated the Museum’s folksong research program in that province. This essay, which is based in part on interviews with Sargent, as well as her field notes and tapes, provides a detailed account of her Newfoundland fieldwork and of the kinds of material she was able to acquire during her one summer of fieldwork. It highlights the fieldwork challenges Sargent faced while in Newfoundland and how her groundbreaking fieldwork paved the way for Peacock’s later research.